Community-based renewable energy from mimosa pigra L. charcoal briquettes - Jolanun, Banjarata; Phutharukchat, Athit; Khamtui, Chansuda Khamtui (Asia-Pacific Journal of Science and Technology, 2017)
This study aimed to develop charcoal briquettes and community-based management of Mimosa Pigra L. residues as a renewable energy source. Results show that the carbonized char was obtained at about 20% by mass and the heating value was increased to 15-36% after carbonizing the biomass and converting the char into briquette. All briquettes (Mimosa Pigra L.) tested were 0.17-0.20±0.01%, 6.8-20.1±0.61-1.01%, 7.0-8.6±0.52-0.84%, 27.3- 32.8±0.71-1.21%, and 44.5-53.5±0.82-1.27% for the sulfur, ash, moisture, volatile matter (VM), and xed carbon content (FC), respectively. The Mimosa Pigra L. briquette with mixed starch binder at 6% was an appropriate condition, under which the maximum heating value (5,432±101.5 cal/g) was achieved, satisfying the Thai Community